(untitled) (Journal of Contemporary Issues in Accounting, 2026)
This study investigated the adoption and implementation of Artificial Intelligence (AI) in forensic accounting practices in Nigeria. The study provides evidence that AI is being adopted and implemented in forensic accounting practices in Nigeria, and that perceived usefulness, organizational culture, and regulatory framework are significant determinants of AI adoption. A survey of forensic Accountants in Nigeria was conducted, and the data was analyzed using regression analysis. The findings of the study showed that perceived usefulness, organizational culture, and regulatory framework have a significant positive impact on the adoption and implementation of AI in forensic accounting practices. The study contributes to the existing literature on AI adoption in accounting and provides insights into the factors that influence AI adoption in forensic accounting practices in Nigeria. The findings of this study have implications for practice, policy, and future research. Forensic accounting firms and organizations can use the findings of this study to inform their technology adoption strategies, while regulatory bodies can develop clear and supportive regulatory frameworks that facilitate the adoption and implementation of AI in forensic accounting practices.